Recalibrating the scale : a case of reseating a sold-out arena - LeCrom, Carrie W.; Slavich, Mark; Rufer, Lisa; Greenhalgh, Greg, active 2016; Dwyer, Brendan (London : Human Kinetics, Inc., 2016)
Reseating a stadium or arena is not a new phenomenon. It offers colleges and universities the opportunity to reward donors who have contributed financially to the athletic department as well as to create or maintain an equitable seat allocation system. At the same time, a poorly planned or poorly executed reseating project has the potential to upset current donors to the point of alienation. ABC University is looking to take on a reseating project, and it is looking to Virginia Commonwealth University for guidance because of its successful 2013 reseating project. With the success of its men's basketball program and highly engaged fan base, the time is right to undertake this project. Factors involved in the decision to reseat, communication with fans, and the method involved with the actual reseating are among the topics discussed. This case study would be beneficial to other schools looking to reseat or future athletic administrators interested in an insider's perspective at a major revenue generation project.
Originally published in LeCrom, C. W., Slavich, M., Rufer, L, Greenhalgh, G., & Dwyer, B. (2016). Recalibrating the scale: A case of reseating a sold-out arena. Case Studies in Sport Management, 5(1), 10-16. DOI:.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Virginia Commonwealth University; ABC University; Sports administration